Análise de áreas para a criação de unidades de conservação no município de Boituva (SP) - Gregorini, Rafael Augusto (Universidade Federal de São Carlos, 2015)
The ongoing concern with environmental problems and the fi nity of natural resources arise the need to create special spaces for the maintenance of natural environment and biodiversity conservation - these areas are called Con servation Units (CUs). This study aims to evaluate the potential for the creation of protected areas according to the SNUC in Vitassay and Rosa Pinhal in the municipality of Boituva and was organized in two articles. In a rticle 1 , the areas were evaluated trough the scoring method, where areas were scored in 11 pre - established criteria. These criteria were analyzed through phytosociological study, rapid ecological assessment and landscape analisys . The score was summed and converted to a scale from 0 to 100 . Fragment 1 (Vitassay) scored 53,48 and Rosa Pinhal scored 76,74 points in 100 possible. The conclusion was that Vitassay can become an "Area of ecological interest" , a sustainable use conservation unit, and Ro sa Pinhal may be settled to an i ntegral p rotection conse rvation unit such as " Natural Municipal Park" . In article 2 w as conducted a phyt osociological analysis trhough plots method. 12 plots of 10x10m w ere demarcated in each of the fragments, distributed in two blocks containing six parcels each, forming a set of 20x30m , measuring 600m² in each of the four areas, 1200m² in Rosa Pinhal and other 1200m² in Vitassay, totaling an area of 2400m² sampled vegetation. The calculations were made using the Fitopac 2.1 application. They sampled 365 individuals belonging to 82 spe cies, 171 individuals and 46 species in the area Rosa Pinhal, and 1 94 individuals and 4 8 species in Vitassay area. The Shannon diversity index (H ') was 3.473 in Rosa Pinhal and 3 . 463 in Vitassay. In Rosa Pinhal the ten species with higher cover values (IV C) totaled 64.5% of the total IVC and , in Vitassay , summed 70.23% of the total IVC. Related to the successional groups in Rosa Pinhal area only 17.3% (8 species) species are pioneers and 67.3% (31 species) not pioneers. In Vitassay 34% (16 species) are pio nner and, 59.5% (28 species) are not pioneer s . Four endangered species were found in Rosa Pinhal and three in Vitassay. The results and analysis allowed the construction of a diagnosis of Vitassay and Rosa Pinhal fragments in the municipality of Boituva an d it was found that both areas have characteristics that favor conservation due to the presence of endangered species and diversity found in this fragments.
Keywords: Áreas de conservação de recursos naturais; Biodiversidade; Natural resources conservation areas; Biodiversity; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA